Pemanfaatan Limbah Plastik dan Kaca Sebagai Subtitusi dalam Pembuatan Roster - Naufal Azhary Handoko; Ghanny Wijaya Kusuma; Hartono Hartono; Riza Susanti (Jurnal Sipil dan Arsitektur, 2025)
Ventilation block is generally made from concrete, namely using cement, sand and water. However, along with the rampant development in Indonesia, cement and sand production has increased, which has had an impact on the environment, namely the level of soil fertility which is increasingly decreasing due to mining and the production of carbon dioxide is increasing. This encourages innovation that can reduce environmental impacts. For this reason, research was carried out on the use of plastic and glass waste as substitute materials for cement and sand in making ventilation blocks. This research aims to determine the value of compressive strength, water absorption capacity, physical or visual results, and cost analysis, as well as obtaining the most optimal variations. The method in this research is experimental, namely by making ventilation block test objects with variations R1 (25%:75%:0%:0%),  R2  (15%:70%:10%:5%),  R3  (20%:65%:5%:10%), R4 (10%:75%:15%:0%), and R5 (25%:60%:0%:15%). The optimum variation results are in the R2 variation with a compressive strength value of 1.8 MPa, water absorption capacity of 3.48%, physical requirements, and a cost of IDR 5.127. Apart from that, variations in R2 can reduce the use of cement by 12.3% and sand by 1.7%. From the test results, the use of plastic and glass waste as a substitute material in making ventilation block can be used because it meets the requirements of SNI 03-0349-1989 or is better than rosters in general and is more environmentally friendly.